Possibilities to adapt oral history to the research of Soviet and post-Soviet epoch (the problems of the culture of memory and the politics of history) - Aurimas Švedas (Lietuvos Istorijos Studijos)
The Soviet epoch often imposes a professional challenge to a researcher due to the complexities of correct analysis and interpretation of the phenomena and processes of that epoch. All that was left by this epoch, which lasted almost half a century, was fragmentary, uninformative, and contradictory written sources which consciously mislead the researcher by not only preventing an answer to the question "what was it really like?", but also by trying to wrap the researcher in a spider web of reticence, Aesopian language, and open lies. The lack or fragmentation and uninformative nature of the written sources forces historians to use in their research the method of oral history interviews which offers many new perspectives. It could provide much help to the new generation of Sovietologists in Lithuania who adapt the potential method of interview primarily while preparing doctoral theses.